Sea fog [videorecording (DVD)] - Sim, Sŏng-bo, 1972-; Kim, Yun-sŏk, 1968-; Pak, Yu-ch'ŏn, 1986-; Han, Ye-ri, 1984-; Kim, Min-jŏng, 1974- (Film Movement series, 2016)
"Haemoo depicts the harrowing events that unfold in the fog-covered seas for a fishing crew engaged in human smuggling. Award-winning actor Kim Yoon Seok stars as the struggling captain who turns to human smuggling in order to keep his fishing boat financially afloat. While transporting ethnic Koreans from China across the Yellow Sea, however, things go terribly wrong, and desperation spirals into tragedy and terror"--YesAsia.com.